Variabilidade temporal no transporte de sedimentos no rio Ivaí - Paraná (1977-2007) - Leli, Isabel Terezinha [UNESP]; Stevaux, Jose Cândido; Nóbrega, Maria Tereza Da; Souza, Edvard Elias De (Sociedade Brasileira de Geologia, 2011)
This paper evaluates the behavior of suspended sediment load of the river Ivaí over a period of 32 years measured by the station further downstream the river (Novo Porto Taquara). The most suitable parameters for this assessment were the annual discharge of suspended sediment and water obtained from SUDERSA. The relationship between the concentration of suspended sediment and discharge of water had not a very good correlation (R2 = 0,56) and hysteresis effect is quite clear. The justification for this behavior is given by the heterogeneity of the hydrological regime and basin occupation. There were no significant changes in annual flows which have remained the same during the study period. Already the discharge of suspended sediment showed a small gradual decline in which the end of the period (2007), the river carries less than 0.65 Mton at the beginning (1977). This reduction in suspended sediment transported is probably due to changes in soil management for agriculture.

Este trabalho avalia o comportamento da carga sedimentar suspensa do rio Ivaí num período de 30 anos aferidos por sua estação mais jusante de Novo Porto Taquara. Os parâmetros utilizados neste estudo foram as descargas anuais de sedimento suspenso e de água obtidas a partir de dados da SUDERSA. A relação entre a concentração de sedimento suspenso e a descarga de água não apresentou uma correlação muito boa (R2 = 0,56), sendo bastante evidente o efeito de histerese. A justificativa para esse comportamento é dada pelo regime hidrológico heterogêneo e pela ocupação da bacia. Não foram observadas alterações significativas nas vazões anuais, que permaneceram as mesmas durante o período estudado. Já a descarga de sedimento suspenso apresentou um pequeno declínio gradual mostrando que no final do período (2007), o rio transporta 0,65 Mton menos do que no começo (1977). Esta redução de sedimento suspenso transportado é provavelmente devido a alterações no manejo do solo para o cultivo agrícola.
Temporal variability in transportation of sediment in the river Ivaí - Paraná (1977-2007)
Keywords: suspended sediment; river regime; basin management; river flow; river discharge; sedimento suspenso; regime fluvial; manejo de bacia; vazão fluvial; descarga fluvial